The Role of Career and Wage Incentives in Labor Productivity: Evidence from a Two-Stage Field Experiment in Malawi - Kim, Hyuncheol Bryant; Kim, Seonghoon; Kim, Thomas T. (The Review of Economics and Statistics, 2020)
We study how career and wage incentives affect labor productivity through self-selection and incentive effect channels using a two-stage field experiment in Malawi. First, recent secondary school graduates were hired with either career or wage incentives. After employment, half of the workers with career incentives randomly received wage incentives, and half of the workers with wage incentives randomly received career incentives. Career incentives attract higher-performing workers than wage incentives do, but they do not increase productivity conditional on selection. Wage incentives increase productivity for those recruited through career incentives. Observable characteristics are limited in explaining selection effects of entry-level workers.